2021
DOI: 10.1172/jci.insight.143474
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Wee1 as a target in combination with avapritinib for gastrointestinal stromal tumor treatment

Abstract: Management of gastrointestinal stromal tumors (GISTs) has been revolutionized by the identification of activating mutations in KIT and PDGFRA and clinical application of RTK inhibitors in advanced disease. Stratification of GISTs into molecularly defined subsets provides insight into clinical behavior and response to approved targeted therapies. Although these RTK inhibitors are effective in most GISTs, resistance remains a significant clinical problem. Development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Recent studies have shown that WEE1 is implicated in multidrug resistance, particularly to drugs related to cell cycle modulators, DNA‐damaging agents, or DNA‐repair inhibitors. Consistently, the drug resistance of tumors is associated with increased expression of WEE1 or activation of WEE1 signaling pathways 11,20 . Indeed, several reports have shown the synergistic effect of the WEE1 inhibitor with various anticancer agents in a variety of malignant diseases, such as the AURKA inhibitor alisertib (MLN8237) in HNSCC, 14 an ATR inhibitor in diffuse large B‐cell lymphoma, 15 a BET inhibitor in non‐small‐cell lung cancer, 35 trastuzumab in HER2‐positive breast cancer, 36 and avapritinib in gastrointestinal stromal tumors 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that WEE1 is implicated in multidrug resistance, particularly to drugs related to cell cycle modulators, DNA‐damaging agents, or DNA‐repair inhibitors. Consistently, the drug resistance of tumors is associated with increased expression of WEE1 or activation of WEE1 signaling pathways 11,20 . Indeed, several reports have shown the synergistic effect of the WEE1 inhibitor with various anticancer agents in a variety of malignant diseases, such as the AURKA inhibitor alisertib (MLN8237) in HNSCC, 14 an ATR inhibitor in diffuse large B‐cell lymphoma, 15 a BET inhibitor in non‐small‐cell lung cancer, 35 trastuzumab in HER2‐positive breast cancer, 36 and avapritinib in gastrointestinal stromal tumors 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, the drug resistance of tumors is associated with increased expression of WEE1 or activation of WEE1 signaling pathways 11,20 . Indeed, several reports have shown the synergistic effect of the WEE1 inhibitor with various anticancer agents in a variety of malignant diseases, such as the AURKA inhibitor alisertib (MLN8237) in HNSCC, 14 an ATR inhibitor in diffuse large B‐cell lymphoma, 15 a BET inhibitor in non‐small‐cell lung cancer, 35 trastuzumab in HER2‐positive breast cancer, 36 and avapritinib in gastrointestinal stromal tumors 20 . These findings suggest that WEE1 is induced by drug treatment as a process toward resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Wells were then treated with varying doses of MK-4440 and/or IM. Cell proliferation and viability were measured at 72 h post treatment using the CellTiter Blue Viability Assay (Promega, Fitchburg, WI, USA) as described previously [24]. Assays were performed as three independent biological replicates, with a minimum of six technical replicates in each treatment arm.…”
Section: Cell Proliferation/viability Assaymentioning
confidence: 99%
“…Assays were performed as three independent biological replicates, with a minimum of six technical replicates in each treatment arm. Combination indexes of CI LD50 (GIST-T1) and CI LD30 (GIST430, GIST-T1/829) were quantified using the previously described approach [24].…”
Section: Cell Proliferation/viability Assaymentioning
confidence: 99%
See 1 more Smart Citation